Liquid transport in non-uniform capillary fibrous media. Issue 9 (May 2019) - Fan, Jie; Li, Cai-Xia; Qi, Yuan-Yuan; Wang, Li-Li; Shou, Wan; Liu, Yong
Liquid transport in porous materials is affected significantly by the geometry of the non-uniform capillaries. In this study, an N -section lotus-rhizome-node-like non-uniform capillary model was for the first time proposed based on the plane Poiseuille flow and capillary pressure equation to investigate the liquid transport in porous fibrous media. Normalized total flow time of the non-uniform capillary was obtained as a function of the height and width ratio between the converging and diverging nodes and their total number. The results indicated that the velocity of liquid transport greatly depended on the number of nodes in a certain liquid transport length. The non-uniform capillaries with frequent alterations between converging and diverging nodes have low liquid transport efficiency. The thick capillary exhibits fast liquid transport efficiency in those capillaries with the same self-similar geometry. The model was verified using polypropylene filament yarns and different liquids. The results agreed well with the theoretical prediction. This work not only provides a deeper understanding of liquid transport inside porous fibrous media with non-uniform capillaries, but can also guide the novel design and optimization of functional fibrous materials.